Stratification of preoperative risk in elderly patients in cardiac surgery clinic - R. A. Gaifullin; S. V. Ivanov; E. N. Gaifullina (Кардиоваскулярная терапия и профилактика, 2020)
In recent decades, population aging has created many problems for the health care system. Along with the main risk factors, including the frequency and severity of comorbidities, elderly patients are subject to changes associated with the aging. It leads to a high probability of adverse events and make it difficult to stratify the risk of patients undergoing cardiac surgery. This review presents data on the preoperative risk stratification in elderly surgical patients.